2020
DOI: 10.1021/acs.energyfuels.0c00477
|View full text |Cite
|
Sign up to set email alerts
|

Olefin Saturation Using Asphaltenes As a Hydrogen Source

Abstract: To facilitate the pipeline transport of oilsands bitumen, bitumen viscosity must be decreased. Decreasing bitumen viscosity by whatever means adds to the production cost of bitumen. One of the low cost methods to decrease bitumen viscosity is mild thermal cracking by visbreaking. Thermally cracked products are potentially fouling in nature and the maximum olefin content of upgraded bitumen is limited by pipeline specifications to reduce risk of fouling. Hydrotreating is conventionally applied to treat cracked … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 17 publications
0
7
0
Order By: Relevance
“…It is worth noting that both light and medium (<350 °C) and heavy (350−500 °C) distillate fractions of oil, industrial solvents, and byproducts can be effective H-donors in visbreaking and under certain conditions, even asphaltenes can function as a source of hydrogen. 34,35 3.2. Characterization of Visbreaking Products.…”
Section: Resultsmentioning
confidence: 99%
“…It is worth noting that both light and medium (<350 °C) and heavy (350−500 °C) distillate fractions of oil, industrial solvents, and byproducts can be effective H-donors in visbreaking and under certain conditions, even asphaltenes can function as a source of hydrogen. 34,35 3.2. Characterization of Visbreaking Products.…”
Section: Resultsmentioning
confidence: 99%
“…Such thermal hydrogenation of alkenes was demonstrated for the treatment of cracked naphtha using asphaltenes as hydrogen source. 45…”
Section: Discussionmentioning
confidence: 99%
“…The longer residence time at temperatures sufficiently high for a high rate of hydrogen transfer could be responsible for alkene saturation. Such thermal hydrogenation of alkenes was demonstrated for the treatment of cracked naphtha using asphaltenes as hydrogen source …”
Section: Discussionmentioning
confidence: 99%
“…One potential application of this concept that was evaluated was to employ the asphaltenes separated by solvent deasphalting as a hydrogen source for transfer to cracked naphtha from thermal conversion by a process such as visbreaking. It was reported that this olefin-treating concept was technically feasible and that 60% olefin conversion in cracked naphtha could be achieved by soaking the cracked naphtha with asphaltenes in a 1:4 ratio for 3 h at 350 °C . The asphaltenes used in the process became a sacrificial hydrogen donor.…”
Section: Technologies For Partial Upgradingmentioning
confidence: 99%
“…It was reported that this olefin-treating concept was technically feasible and that 60% olefin conversion in cracked naphtha could be achieved by soaking the cracked naphtha with asphaltenes in a 1:4 ratio for 3 h at 350 °C. 76 The asphaltenes used in the process became a sacrificial hydrogen donor.…”
Section: Solvent Deasphaltingmentioning
confidence: 99%